Analysis of Wear in UHMWPE Artificial Hip Joint Using Finite Element Method: A Review - Wahyudi, Mujib; Nur, Achmad Zain (Sains Data Jurnal Studi Matematika dan Teknologi, 2024)
Ultra-high-molecular-weight polyethylene (UHMWPE) is one of the most commonly used materials in the fabrication of artificial hip joints due to its excellent mechanical properties, biocompatibility, and wear resistance. Despite its advantages, the wear of UHMWPE components over time leads to the generation of wear particles, which are responsible for osteolysis and implant failure. The Finite Element Method (FEM) has emerged as a powerful tool to simulate the wear mechanisms of UHMWPE in hip implants, providing a deeper understanding of the stress distribution, wear prediction, and optimization of implant designs. This review explores the current state of FEM applications in UHMWPE wear analysis, focusing on the material properties, wear mechanisms, FEM simulation models, and future directions in this research area.